Can Indonesian Nurses Against Covid-19? - Kartika, Imelda Rahmayunia; Rezkiki, Fitrianola (Universitas Fort De Kock Bukittinggi, 2021)
At the beginning of 2020, the world was shaken by the spread of new viruses, the new type of coronavirus (SARS-Cov-2), and the disease was called the Corona Virus Disease-2019 (COVID-19). As of 20 May 2020, In Indonesia were reported 19,189 cases with 1,242 deaths (CFR 6.47%) including nurses (55 health workers are death). There was a shocking lack of preparedness at hospitals in handling this, which puts nurses at particular risk. Nurses claimed to have difficulty getting PPE (Personal Protective Equipment). In addition, the cases of nurses who were stigmatized in their environment due to exposure to the COVID-19 were very widespread, even in the funeral process they were still rejected. Many things can be done to increase the ability of Indonesian nurses in their devotion when handling COVID-19. It can be from the nurses themselves, professional organization support, government support, and community support. The appreciation can also help them struggle to fight against COVID-19. In the future, when this pandemic is over, we need to appreciate what nurses have done for the world.Keywords: Nurses, against, covid-19